2015
DOI: 10.4236/jamp.2015.312182
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection MHD Flow of a Casson Nanofluid over a Nonlinear Permeable Stretching Sheet with Viscous Dissipation

Abstract: The present study deals with the mixed convection MHD flow of a Casson nanofluid over a nonlinear permeable stretching sheet with viscous dissipation. The governing partial differential equations are transformed into nonlinear coupled ordinary differential equations with the help of suitable similarity transformations. These equations were then solved numerically by using an implicit finite difference method known as Keller-Box method. The effects of various parameters such as magnetic parameter (M), Casson pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(25 reference statements)
2
10
0
Order By: Relevance
“…Mahdy and Chamka (2015) take on Buongiorno's model to study Casson nanofluid flow and observe that Casson parameter restrain the velocity field. Besthapu and Bandari (2015) studied Casson nanofluid flow on a nonlinear elongated sheet concluded that enhancement in Grashoff number reduces the temperature of the fluid. Uddin et al (2015) described Casson fluid flow with slip parameter and observed that increasing thermal slip nanoparticles concentration would be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdy and Chamka (2015) take on Buongiorno's model to study Casson nanofluid flow and observe that Casson parameter restrain the velocity field. Besthapu and Bandari (2015) studied Casson nanofluid flow on a nonlinear elongated sheet concluded that enhancement in Grashoff number reduces the temperature of the fluid. Uddin et al (2015) described Casson fluid flow with slip parameter and observed that increasing thermal slip nanoparticles concentration would be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Khalid et al [18] explored the influence of the magnetic field and the heat supply on a CNF steady flow and heat transmit over an exponentially expanding cylinder over its radial path. Besthapu et al [19] tested in a porous substance with wall temperature, MHD time-dependent Casson fluid running over a vertical surface. Imtiaz et al [20] probed CNF mixed convection magneto flow via a non-linear permeable extending plate with the viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…This study was extended by Das [ 8 ] and Hayat et al [ 9 ], who used partial slip conditions for the boundary layer flow to investigate the velocity, temperature and concentration changes with regard to various dimensionless parameters in the fluid flow under the influence of a magnetic field. Besthapu and Bandari [ 10 ] have analysed the heat and mass transfer rates using Casson nanofluids with nonlinear equations. Applications in nuclear waste storage were initiated by Gaffar et al [ 11 ], who focussed on viscoelastic Jeffrey fluid in a porous medium considering the effect of various dimensionless parameters that influence the heat and mass transfer flow.…”
Section: Introductionmentioning
confidence: 99%